Biology, ecology, population dynamics and distribution of metals in Sepia officinalis on a typical estuarine coastal lagoon - Ria de Aveiro - Dias, Cláudia Pessoa (2015)
The common cuttlefish, Sepia officinalis, is a necto-benthic cephalopod that can live in coastal ecosystems, with high influence of anthropogenic pressures and thus be vulnerable to exposure to various types of contaminants. The cuttlefish is a species of great importance to the local economy of Aveiro, considering the global data of catches of this species in the Ria de Aveiro. However, studies on this species in Ria de Aveiro are scarce, so the present study aims to fill this information gap about the cuttlefish in the Ria de Aveiro. The cuttlefish enters Ria de Aveiro in the spring and summer to reproduce, returning to deeper waters in the winter. In terms of abundance, the eastern and center regions of the lagoon, closer to the sea, showed the highest values of abundance, while the northern and southern regions of the main channel had the lowest abundance. This fact may be related to abiotic factors, as well as depth, salinity and temperature. In the most southern point of the Ria de Aveiro (Areão) no cuttlefish was caught. This site had the lowest values of salinity and depth. The cuttlefish has an allometric the females being heavier than males to mantle lengths greater than 82.4 mm. Males reach sexual maturity first than females. In Ria de Aveiro in a generation of parents was found. The cuttlefish, presents itself as opportunistic predators, consuming a wide variety of prey from different taxa. The diet was similar in different sampling locations observing significant differences for the seasons. S. officinalis was captured at 10 sites in the Ria de Aveiro with different anthropogenic sources of contamination. Thus, levels of metals analyzed were similar at all sampling sites, with the exception of a restricted area, Laranjo, which showed higher values. The cuttlefish has the ability to accumulate metals in your body. The levels of Fe, Zn, Cu, Cd, Pb and Hg found in the digestive gland and mantle reflect a differential accumulation of metals in the tissues. This accumulation is related to the type and function of tissue analyzed and the type of metal analysis (essential and non-essential). The metal concentrations in the digestive gland are higher than in the mantle, with the exception of mercury. This may be due to the high affinity of the mantle for the incorporation of methylmercury (MeHg), the most abundant form of mercury. The accumulation of metals can vary over a lifetime, depending on the metal. The concentrations of Zn, Cd and Hg increases throughout life, while Pb decreases and essential metals such as Fe and Cu remain constant. The data collected suggest that the cuttlefish (Sepia officinalis) can be used as a bioindicator of environmental contamination for some metals.